2019
DOI: 10.1084/jem.20182293
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis of RORα tracer mouse lung reveals ILC progenitors and effector ILC2 subsets

Abstract: Lung group 2 innate lymphoid cells (ILC2s) drive allergic inflammation and promote tissue repair. ILC2 development is dependent on the transcription factor retinoic acid receptor–related orphan receptor (RORα), which is also expressed in common ILC progenitors. To elucidate the developmental pathways of lung ILC2s, we generated RORα lineage tracer mice and performed single-cell RNA sequencing, flow cytometry, and functional analyses. In adult mouse lungs, we found an IL-18Rα+ST2− population different from conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
77
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 77 publications
11
77
1
1
Order By: Relevance
“…To this end, we sort-purified Il18r1 +-ST2 À and Il18r1 À ST2 + ILCs from lungs 2 days (d) post infection (p.i.) and co-transferred cells at a 1:1 ratio into sublethally irradiated RAGgc À/À hosts, as previously established (Ghaedi et al, 2020;Xu et al, 2019). Three weeks after transfer, we found that Il18r1 + ST2 À cells partly gave rise to Il18r1 + ST2 À , Il18r1 + ST2 + , and Il18r1 À ST2 + ILC2s, consistent with the idea that these cells can differentiate into mature ILC2s ( Figure 3K).…”
Section: Heterogeneity Of Ilc2s In Healthy Lung Tissuesupporting
confidence: 88%
See 1 more Smart Citation
“…To this end, we sort-purified Il18r1 +-ST2 À and Il18r1 À ST2 + ILCs from lungs 2 days (d) post infection (p.i.) and co-transferred cells at a 1:1 ratio into sublethally irradiated RAGgc À/À hosts, as previously established (Ghaedi et al, 2020;Xu et al, 2019). Three weeks after transfer, we found that Il18r1 + ST2 À cells partly gave rise to Il18r1 + ST2 À , Il18r1 + ST2 + , and Il18r1 À ST2 + ILC2s, consistent with the idea that these cells can differentiate into mature ILC2s ( Figure 3K).…”
Section: Heterogeneity Of Ilc2s In Healthy Lung Tissuesupporting
confidence: 88%
“…Furthermore, single-cell transcriptome comparisons of ILC populations in the BM, neonatal, and adult lung at steady state, as well as over the course of helminth infection in wildtype, parabiotic, and shield chimeric mice support the idea that core programs of ILC2 differentiation are recapitulated during ontogeny as well as inflammatory challenge. Systemic ILC progenitors in men exhibit a transcriptional profile reminiscent of Il18r1 + ILCPs in murine lung (Ghaedi et al, 2020;Lim et al, 2017). We confirmed that these cells are present in human lung tissue and can be further characterized by IL18R1 and TCF1 expression.…”
Section: Discussionsupporting
confidence: 73%
“…26 As tissue-resident cells, ILCs integrate into the organ milieu and only circulate in the bloodstream in low numbers but are often replenished by local precursors. [27][28][29] This notion is supported by parabiosis experiments where mainly donor-derived adaptive lymphocytes and NK cells, but not other ILCs subsets could be recovered from the recipient's tissues at steady state. 26,30,31 During worm infection, ILC2s and in particular inflammatory ILC2s can leave their environment and are disseminated to other tissues via the bloodstream.…”
Section: Introductionmentioning
confidence: 89%
“…While the activity of ILC2-derived amphiregulin in tissue repair has not been studied in helminth models, it is likely to play a role as its expression is increased 12 days after N. brasiliensis infection (105). More recently, it was suggested that amphiregulin-producing ILC2s are a subset distinct from IL-5/IL-13-producing ILC2s (111). This study assessed pulmonary ILC2s at steady state in neonatal mice and used gene expression profiles to separate ILC2s into either Klrg1/Il5/Il13-or Icos/amphiregulin-expressing subsets.…”
Section: Ilc2 Functionmentioning
confidence: 99%
“…Although in vivo support is limited, one study describes the requirement of Notch signaling for the generation of iILC2s, and when nILC2s were cultured on Notch ligandexpressing cells they adopted an iILC2 phenotype and gained the ability to produce IL-17 (130). Additionally, IL-18Rα + ILC precursors have recently been reported in the murine lung that are capable of giving rise to nILC2s (111). It would be of interest to assess whether this lung tissue-resident precursor subset can also differentiate into iILC2s during helminth infection.…”
Section: Origin Of Iilc2smentioning
confidence: 99%